The Application of Anatomy Combined With Ultrasound Knife in Transaxillary Endoscopic Biplane Breast Augmentation - Xiong, Jiachao; Hou, Qiang; Hu, Zheyuan; Gao, Yakun; Lu, Lu; Sun, Meiqing; Hu, Hao; Qian, Yuxin; Wang, Hui; Jiang, Hua (Frontiers in Surgery, 2022)
Objective: We aim to clarified the vascular and nerve anatomy of the breast and combine with ultrasound knife to use in transaxillary endoscopic biplane breast augmentation. Methods: This study is a retrospective review of patients undergoing transaxillary endoscopic biplane breast augmentation between October 2019 and October 2021. Related variables were collected using a standardized data collection template. The detailed process of the transaxillary endoscopic biplane breast augmentation under anatomy instruction is carefully described in this study, and the postoperative effect was closely observed. Results: Sixty-three female patients underwent transaxillary endoscopic biplane breast augmentation between October 2019 and October 2021. The average implants volume counted 242.46  31.34 cc. Most of the patients achieved good postoperative results and no severe complications, and were satisfied with both appearance and function. Conclusions: The application of anatomy combined with ultrasound knife in transaxillary endoscopic biplane breast augmentation is a promising way to achieve good breast shapes with high patient satisfaction and is worthy of clinical promotion and application.